THE EFFECTIVENESS OF USING MIND MAPPING TECHNIQUE ON STUDENT ACHIEVEMENT OF READING NARRATIVE TEXT - Sulistiani, Endah (Pusat Pengembangan Bahasa IAIN Tulungagung, 2014)
Mind mapping is one of the techniques in teaching reading that the students make a map after they read a text. In Mind-mapping technique, The students read a text. After reading a text, the students must make a map about a text that they have read. This technique will make students understand and memorize the text easily. The result showed that The Tcount was 8.549, whereas Ttable with significant level 5% was 2.021. So, Tcount was bigger than Ttable. It means that Ha which states that there is significant different in using mind-mapping technique to teach reading to the second grade at MTs N Bandung is accepted. Whereas, Ho which states that there is no significant different of using mind-mapping technique to teach reading to the second grade at Mts N Bandung is rejected.